Integrated weed management strategies for delaying herbicide resistance in wild oats - Thill, D.C.; O’Donovan, J.T.; Mallory-Smith, C.A. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1994)
Herbicide-resistant biotypes of wild oats (Avena fatua) infest most major cereal producing regions in the western United States and Canada. This paper reviews potential integrated weed management strategies that can be used to prevent or delay selection of herbicide-resistant wild oats plants. An integrated wild oats management strategy to delay or prevent the development of herbicide resistance should be based on preventing the movement of wild oats seed into the soil. Two ways to achieve this are by preventing the immigration of seed into the field from external sources, and by reducing or eliminating seed production by wild oats already in the field. It is becoming increasingly clear that reliance on continuous herbicide useas the sole means of weed control will fail to eliminate wild oats and other weed seed from the soil seedbank. On the contrary, evidence is mounting that this practice will select for biotypes that are resistant to the herbicides used, especially where herbicides of the same mode of action are used continuously. It is essential, therefore, that herbicides be considered as just one component of an overall integrated System together with cultural control and other management strategies, and that agronomic principles be considered when developing this System.